PERCEPTIONS OF FAITH-BASED TOURISM INFORMATION AND BELIEFS OF TOURISTS IN NAKHON SI THAMMARAT PROVINCE - Wangboonkong, Patarawan; Kitsanarom, Nuchanart; Khongphan, Phiangchai; Jutidharabongse, Jaturon (Journal of MCU Nakhondhat, 2026)
This quantitative study employed a survey research design. Its objectives were: 1) To investigate tourists’ awareness of information concerning faith-based tourism and beliefs in Nakhon Si Thammarat Province; and 2) To examine the relationships between tourists’ demographic characteristics and their selection of faith-based tourism routes in the province; and 3. to examine the relationships between tourists’ demographic characteristics and public relations media channels. The sample comprised 400 tourists who had previously visited Nakhon Si Thammarat Province. Data were analyzed using frequencies, percentages, the chi-square test, and Cramér’s V. The findings revealed that tourists’ awareness of faith-based tourism and beliefs was concentrated around particular destinations. The Maha Setthi (Wealth and Prosperity) Route was predominantly associated with Wat Chedi (Ai Khai); the Maha Metta Maha Niyom (Charm and Popularity) and Maha Keji (Revered Masters) routes were predominantly associated with Wat That Noi (Phor Than Klai Wajasit); and the Maha Mongkhon (Auspicious) Route was predominantly associated with Wat Phra Mahathat Woramahawihan. The perceived sacredness of the destinations and ease of travel were important factors influencing tourists’ awareness and route selection. The principal information channels were Facebook, television, and word of mouth from family members, friends, and other close contacts. Income was the demographic variable most consistently associated with route selection and information channels, followed by educational attainment and age. These findings indicate that faith-based tourists may be segmented according to their economic capacity and social capital. By contrast, occupation exhibited relatively limited associations with tourism behavior. The findings can be applied to the development of targeted marketing and communication strategies for faith-based tourism, the dispersal of tourists across alternative routes to reduce concentration at major destinations, and the sustainable enhancement of the creative economy based on the cultural heritage and belief systems of Nakhon Si Thammarat Province.